Analisis Debit Andalan Untuk Kebutuhan Air Daerah Irigasi Sungai Lamasi Pada Das Pompengan Kab Luwu - Muh Rezky Syahban; Suryani Syahrir; Burhanuddin Badrun (Program Studi Teknik Sipil Universitas Bosowa, 2026)
The Pompengan Watershed area is located in 2 administrative areas of regencies/cities, namely North Toraja Regency and Palopo Regency. The Pompengan Watershed is elongated with an area of 514.24 km2. The Pompengan Watershed has a main river, namely the Lamasi River with a length of approximately 40.5 km, a width of 40 m - 10 m. Lamasi River Irrigation Area In the Pompengan Watershed, Luwu Regency, a hydrological analysis of water availability was carried out using the F.J. Mock method The aim is to determine the Main Discharge and water availability to irrigate the Lamasi left irrigation area which is 3854 ha and Lamasi right with an area of 3839 ha. The calculation results show that the monthly Main Discharge value of the Lamasi River in the Pompengan Watershed, Luwu Regency, the largest average value is in the rainy season, namely March - July with a value of 54.503 m / second and the smallest in the dry season, namely August - February with a value of 0.017 m / second. The water discharge of Lamasi River in the Pompengan Watershed, Luwu Regency, which can be used for irrigation water availability using 80% reliability, where the results obtained with the largest value were in April - July, with an average value of 2,821 m/second3